2003
DOI: 10.1677/jme.0.0300197
|View full text |Cite
|
Sign up to set email alerts
|

A specific and unusual nuclear localization signal in the DNA binding domain of the Rev-erb orphan receptors

Abstract: The orphan receptors Rev-erbα and Rev-erbβ are members of the nuclear receptors superfamily and act as transcriptional repressors. Rev-erbα is expressed with a robust circadian rhythm and is involved in liver metabolism through repression of the ApoA1 gene, but no role has been yet defined for Rev-erbβ. To gain better understanding of their function and mode of action, we characterized the proteins encoded by these two genes. Both Rev-erbα and Rev-erbβ proteins were nuclear when transiently transfected in COS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 54 publications
0
15
1
Order By: Relevance
“…The mechanism for nonnuclear localization of HNF4␣ induced by PKC may involve interference with the positively charged residues (R76, R77, R80, and K81) that surround S78, which comprise an NLS. This region has also been shown to be an NLS for other NRs (60)(61)(62)(63)(64), although until now there has not been a detailed examination of the effect of PKC phosphorylation of 'S78' on nuclear localization. Here, we show that 'S78' (T162) in the RXR␣ DBD is phosphorylated by PKC and that introduction of a single negative charge at that position results in a remarkable cytoplasmic localization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism for nonnuclear localization of HNF4␣ induced by PKC may involve interference with the positively charged residues (R76, R77, R80, and K81) that surround S78, which comprise an NLS. This region has also been shown to be an NLS for other NRs (60)(61)(62)(63)(64), although until now there has not been a detailed examination of the effect of PKC phosphorylation of 'S78' on nuclear localization. Here, we show that 'S78' (T162) in the RXR␣ DBD is phosphorylated by PKC and that introduction of a single negative charge at that position results in a remarkable cytoplasmic localization.…”
Section: Discussionmentioning
confidence: 99%
“…The sequence of the other NR DBDs with a Ser or Thr at that position also match the PKC consensus but to varying degrees. This region of the NR DBD has been shown to be important for nuclear localization of RXR, VDR, SXR, and the Rev-erb receptors (60)(61)(62)(63)(64). In addition, the conserved serine has been shown to be a target of PKC phosphorylation in VDR (S51) and PPAR␣ (T129) (35,38).…”
Section: A Conserved Ser/thr In the Nr Dna Binding Domain Fits The Pkmentioning
confidence: 99%
“…Further, although Rev-erb␣/␤ have been shown to be predominantly nuclear proteins (87), the effect of heme on Rev-erb␤ subcellular localization has not been tested. We transiently transfected HEK293 cells with expression vectors for the wildtype, H568F, and H568F/C384A forms of Rev-erb␤, fractionated the cells into cytosolic and nuclear compartments, and determined the relative amounts of Rev-erb␤ in each fraction (Fig.…”
Section: An Unknown Factor Present In Cell Extracts Mediates the Hemementioning
confidence: 99%
“…However, we did not detect significant NLS activity in the corresponding regions of LRH-1. The absence of a NLS in the LBD has also been reported for another orphan receptor Rev-erb [41]. Structural and biochemical analysis showed that the activation of mouse LRH-1 is ligand-independent, whereas the binding of phosphatidyl inositol can regulate the activity of human LRH-1 and mouse and human SF-1 [13,42].…”
Section: Discussionmentioning
confidence: 56%